An analysis of the measures to counter cyber attacks / Ummi Hani’ Maso’od - Maso’od, Ummi Hani’ (2014)
Cyber attacks have been increasingly acknowledged as a new technological method to wage war. States perceive cyber attacks as a threat to the national security especially the critical national infrastructure. The 2007 incident in Estonia illustrates the severity of the impact of cyber attacks. Estonia’s banking, media and government websites were bombarded with Distributed Denial of Service (DDOS) attacks. The attacks crippled the administration and banking system of Estonia for three weeks. Recent years have seen the alarming rise of premeditated cyber attacks with potentially catastrophic effects to the information systems and networks across the globe. The focus of this study is to assess the role of the state and to investigate the measures in countering cyber attacks. This study examines related international and regional instruments, states’ practice, domestic legislations, and scholarly writing for the purpose of identifying the measures adopted by states in dealing with cyber attacks. The findings from this study demonstrate that strategies to counter cyber attacks are divided into non-criminal enforcement and criminal liability. Currently, states are focusing on non-criminal enforcement measures such as engaging private entities to strengthen their cyber security. Criminal law have not been fully utilised at this moment in dealing with cyber attacks. This study argues that an integrated approach, which combines non-criminal enforcement and criminal liability, may provide the best solution to counter cyber attacks